Enhancement of Tissue-type Plasminogen Activator-induced Thrombolysis and Prevention of Reocclusion by Combination with a Humanized Anti-glycoprotein IIb/IIIa Monoclonal Antibody, YM337, in a Rhesus Monkey Model of Coronary Thrombosis - Kawasaki, Tomihisa; Sato, Kazuo; Suzuki, Ken-ichi; Sakai, Yumiko; Taniuchi, Yuta; Kaku, Seiji; Yano, Shinya; Inagaki, Osamu; Tomioka, Kenichi; Masuho, Yasuhiko; Yanagisawa, Isao; Takenaka, Toichi (Thrombosis and Haemostasis, 1998)
We examined the effect of a humanized anti-glycoprotein IIb/IIIa monoclonal antibody, YM337, on thrombolysis with tissue-type plasminogen activator in a copper coil-induced coronary thrombosis model in rhesus monkeys. Fifty minutes after the formation of an occlusive thrombus, a test drug was administered by either i.v. bolus injection followed by continuous infusion (YM337, 0.25 mg/kg + 1.5 μg/kg/min) or i.v. bolus injection (aspirin, 17 mg/kg). Sixty minutes after induction of the occlusive thrombus, thrombolysis was initiated with tPA at a total dose of 0.5 mg/kg intravenously administered over 60 min, with 10% given as an initial bolus. The median time to reperfusion was significantly shortened by YM337 [saline, 60 min (n = 5); aspirin, 45 min (n = 5); YM337, 30 min (n = 5)]. The incidence of reocclusion was significantly decreased by YM337 (saline, 4/4; aspirin, 5/5; YM337, 1/5), and the median time to reocclusion was significantly prolonged by YM337 [saline, 30 min (n = 4); aspirin, 30 min (n = 5); YM337, 180 min (n = 5)]. YM337 significantly reduced the thrombus protein content at the end of experiment. ADP-induced platelet aggregation was completely inhibited by YM337. These results suggest that YM337 may be of clinical value as an adjunctive agent in thrombolytic therapy for patients with acute myocardial infarction.